A Revenge or a Challenge to Patriarchy? a Feminism Study of Kill Bill Movie - Lisa Andriyani; Teguh Kasprabowo (Pusat Riset dan Inovasi Nasional, 2025)
This research is intended to advance a more comprehensive understanding of how gender is portrayed in movies and how this medium may be used to investigate and discuss feminist problems. Furthermore, this study may give rise to conversations concerning the significance and influence of patriarchal narratives in a broader societal setting, as well as the part that women play in opposing repressive authorities. Qualitative methods are used, screening the film